On the Asymptotic Distribution of the Likelihood Ratio Statistic - Scott, W. F. (Communications in statistics. Theory and methods, 2007)
Likelihood ratio tests are among the most frequently used in practical statistics. Important references on this subject include Wilks ( 1962 ), Rao ( 1965 , pp. 347-352), and Agresti ( 1990 , pp. 434-435). We give proofs of some well-known results on the limiting distribution of D = −2log(λ), where λ is the likelihood ratio, under certain clearly-stated assumptions. We illustrate the theory by means of an example on contingency tables. Although results of this type are frequently used, the underlying theory is not always fully explained.